2016
DOI: 10.4103/0971-5916.195044
|View full text |Cite
|
Sign up to set email alerts
|

Wilms′ tumour 1 gene mutations in south Indian children with steroid-resistant nephrotic syndrome

Abstract: Background & objectives:Clinically, nephrotic syndrome (NS) is a diverse group of symptoms; about 20 per cent of NS cases are resistant to steroid treatment, and within ten years they progress to end-stage renal disease. The present study was undertaken to identify the mutations of Wilms’ tumour 1 (WT1) gene in steroid-resistant NS (SRNS) children.Methods:A total of 173 children with SRNS and 100 children in the control group were enrolled in the study. DNA extraction was done, screened for WT1 (exons 8 and 9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(42 reference statements)
0
1
1
Order By: Relevance
“…However, reports from India including from our center showed that the prevalence of NPHS2 mutations is much lower in Indian population when compared with Europe and North American population [4% vs. 10.5–28%)] [ 7 – 12 ]. Kumar et al, reported low prevalence of WT1 mutation in south Indian population, whereas we did not detect any mutation in WT1 gene in 100 SRNS children [ 13 , 14 ]. These data suggest that a traditional genetic testing using an algorithmic approach based on age of onset of NS to prioritize the genes to be sequenced by Sanger may not be useful [ 15 , 16 ].…”
Section: Introductioncontrasting
confidence: 83%
“…However, reports from India including from our center showed that the prevalence of NPHS2 mutations is much lower in Indian population when compared with Europe and North American population [4% vs. 10.5–28%)] [ 7 – 12 ]. Kumar et al, reported low prevalence of WT1 mutation in south Indian population, whereas we did not detect any mutation in WT1 gene in 100 SRNS children [ 13 , 14 ]. These data suggest that a traditional genetic testing using an algorithmic approach based on age of onset of NS to prioritize the genes to be sequenced by Sanger may not be useful [ 15 , 16 ].…”
Section: Introductioncontrasting
confidence: 83%
“…Genetic and clinical data were obtained from a total of 126 cases: 115 cases described in previous reports 6 , 11 , 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 and 11 cases diagnosed at our institution ( Table 2 ). There were no significant differences in the proportions of patients with female external genitalia and XY chromosomes between the 2 major variants: c.1432+4 C>T (44/49, 90%) and c.1432+5 G>A (30/35, 86%) ( Table 2 , P = 0.57, χ 2 test).…”
Section: Resultsmentioning
confidence: 99%